STRATEGI EVENT MANAGEMENT PT. DBL INDONESIA PASCA PANDEMI (The Commercium, 2023)
This research describes the event management strategies of PT. DBL Indonesia in organizing the Honda DBL With KFC East Java Series North Region 2022 event during the post-pandemic adaptation. To achieve the objectives, a qualitative research method with a case study approach was used. Data collection techniques included observation, interviews, and documentation. The collected data were analyzed through data collection, data reduction, data presentation, and drawing conclusions. The data presentation in this study took the form of written descriptions, presenting the information as it was observed in the field. The results of this research conclude that PT. DBL Indonesia successfully demonstrated adaptive and innovative event management strategies in organizing the basketball event. They built trust among visitors through strict health protocols, created a comprehensive guideline book for post-pandemic event organization, and utilized popular Key Opinion Leaders (KOLs) on social media. Additionally, the well-planned organization of the national student league event contributed to maintaining participant enthusiasm and fostering strong relationships with them. All of these efforts resulted in effective communication and strengthened bonds among participants, students, and supporters of the alma mater